2020
DOI: 10.1177/0956797620948810
|View full text |Cite
|
Sign up to set email alerts
|

Universal Patterns in Color-Emotion Associations Are Further Shaped by Linguistic and Geographic Proximity

Abstract: Many of us “see red,” “feel blue,” or “turn green with envy.” Are such color-emotion associations fundamental to our shared cognitive architecture, or are they cultural creations learned through our languages and traditions? To answer these questions, we tested emotional associations of colors in 4,598 participants from 30 nations speaking 22 native languages. Participants associated 20 emotion concepts with 12 color terms. Pattern-similarity analyses revealed universal color-emotion associations (average simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
7
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(154 citation statements)
references
References 41 publications
13
129
7
5
Order By: Relevance
“…The results of Experiment 1 showed that the associations across the four languages exhibited a high degree of similarity and followed the same overall direction towards the two dimensions of the emotions. These findings are consistent with other studies that have found large similarities in associations between emotions and colors [ 49 , 82 , 97 , 98 ] and emotions and brightness [ 99 ] across languages. The large similarity in temperature-emotion associations can be the result of highly comparable concepts linked to emotions across languages, which can potentially be captured by broad categories.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of Experiment 1 showed that the associations across the four languages exhibited a high degree of similarity and followed the same overall direction towards the two dimensions of the emotions. These findings are consistent with other studies that have found large similarities in associations between emotions and colors [ 49 , 82 , 97 , 98 ] and emotions and brightness [ 99 ] across languages. The large similarity in temperature-emotion associations can be the result of highly comparable concepts linked to emotions across languages, which can potentially be captured by broad categories.…”
Section: Discussionsupporting
confidence: 93%
“…To analyze the overall degree of similarity of the associations across the different languages, Pearson’s correlations ( r ) between each pair of language’s 12 (emotions) × 5 (temperatures) ratings matrices were computed. This procedure was similar to the one used by Jonauskaite et al [ 82 ] to analyze the similarity patterns in the associations of colors and emotions across languages.…”
Section: Methodsmentioning
confidence: 99%
“…blue towards masculinity and positivity. We expected red to be biased towards masculinity, while having no particular valence bias because red carries both positive and negative connotations [23][24][25][26][27]. To this end, we scored embeddings of the colour terms pink, blue, and red, which we obtained from GloVe [39].…”
Section: Plos Onementioning
confidence: 99%
“…Red, on the contrary, represents being in power, dominant, and of high social status [15][16][17][18]. These representations potentially explain why adult women like red [9,[19][20][21][22] and why red carries both positive and negative connotations [23][24][25][26][27]. When it comes to valence, pink and blue both have been associated with mainly positive emotions [24,[27][28][29], although blue has been also associated with sadness [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Интенсивность можно было оценить по шестибалльной шкале (0 -нет эмоции; 1самая слабая эмоция, 5 -самая сильная) (подробнее см. [Jonauskaite et al, 2020]).…”
Section: Introductionunclassified